The Use of Active Learning Strategies in High Schools, Zabul, Afghanistan - Abdul Nafi Himat; Rahmatullah Kakar (International Journal of Evaluation and Research in Education (IJERE), 2022)
The aims of this research were to investigate the use of active learning strategies, the views of teachers towards student-centered techniques, and the factors that hindering the implementation of learner-centered approaches in High Schools. The quantitative method used for this study, and the data collected from the teachers through questionnaire as well they selected through random sampling method. The data analyzed by IBM 24 version of SPSS. The findings of this study indicated that teachers used question and answer, debate, information gap, role-play, think-pair-share, group work, turn and talk, one-minute paper, brainstorming and pair work in the classroom. Moreover, the findings asserted from the views of teachers that active learning strategies give chance to students to participate actively in the teaching, and they focused that these techniques should be applied in classrooms as well as these strategies motivate students. Also, enhance students’ self-confidence. Similarly, the results further asserted that the use of student-centered methods persuade teachers to teach better. Furthermore, the factors that hindering the use of learner-centered strategies were the hard system of education, lack of training, absence of advanced technology in classes, many teaching periods in a week, lack of instructional materials and many students in classrooms.